Fear of Crime and Anti-Refugee Sentiments: Evidence from Canada - Pruysers, Scott; Banerjee, Kiran; Blais, Julie (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2024)
Many states have witnessed growing xenophobia and hostility towards refugees alongside the framing of refugees as a serious security or criminal threat in public discourse. Making use of an original cross-national survey of adults in Canada, this article explores the link between fear of crime and negative views of refugees. Its results reveal that even after controlling for alternative explanations, people with more fear of crime are significantly more likely to express anti-refugee sentiments. These results have implications for understanding ongoing challenges in maintaining domestic support for refugee protection and the importance of dispelling myths that refugees are sources of criminality.